2005
DOI: 10.1021/nl0502569
|View full text |Cite
|
Sign up to set email alerts
|

Optical and MRI Multifunctional Nanoprobe for Targeting Gliomas

Abstract: A multifunctional nanoprobe capable of targeting glioma cells, detectable by both magnetic resonance imaging and fluorescence microscopy, was developed. The nanoprobe was synthesized by coating iron oxide nanoparticles with covalently bound bifunctional poly(ethylene glycol) (PEG) polymer, which were subsequently functionalized with chlorotoxin and the near-infrared fluorescing molecule Cy5.5. Both MR imaging and fluorescence microscopy showed significant preferential uptake of the nanoparticle conjugates by g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
409
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(416 citation statements)
references
References 21 publications
3
409
2
2
Order By: Relevance
“…69 In this case, the contrast agent consisted of a SPIOchlorotoxin peptide conjugate. 148 In another embodiment, SPIO-herceptin was able to mark the HEr-2/neu (c-erb B-2) tyrosine kinase receptor. 9,44 This target has been found to be overexpressed on breast cancer cells in 25% of women with metastatic breast cancer.…”
Section: Cancer Imagingmentioning
confidence: 99%
“…69 In this case, the contrast agent consisted of a SPIOchlorotoxin peptide conjugate. 148 In another embodiment, SPIO-herceptin was able to mark the HEr-2/neu (c-erb B-2) tyrosine kinase receptor. 9,44 This target has been found to be overexpressed on breast cancer cells in 25% of women with metastatic breast cancer.…”
Section: Cancer Imagingmentioning
confidence: 99%
“…Through interaction with MMP-2/MT1-MMP it induces the internalization into caveolar rafts and, within 10-30 minutes depletes Cl − channels from the cell surface. Internalization occurs in conjunction with the Cltx peptide (Deshane et al, 2003) and this feature has been exploited recently to manufacture a Cltx-based multi-functional nanoprobe that either targets glioma cells or detecting them by magnetic resonance imaging and fluorescence microscopy (Veiseh et al, 2005). Moreover, the finding that the molecule is captured intracellularly by tumor cells and, hence, cannot be cleared explains why [131]I-labeled Cltx is still visualized in tumors 8 days after administration in clinical trials (Hockaday et al, 2005).…”
Section: A Putative CL − Channel Inhibitor (Cltx) Is Currently In Climentioning
confidence: 99%
“…However, it has been shown that as the reverse micelle is heated up, improvement of the crystallinity of iron oxide and other ferrite is achieved. [129] In addition, scaling up is complicated due to the sensitivity of preparation conditions, the need for large amounts of organic solvent, and difficulty to remove the surfactants.…”
Section: Reverse Micelle (Microemulsion)mentioning
confidence: 99%